Consumer Behaviour of Mainstream Population towards Ethnic Grocery Retailers in the UK - Vu, Ngoc Phuong Linh (2013)
This research seeks to investigate consumer behaviour of mainstream population towards ethnic minority entrepreneurs in the United Kingdom based on the explorative study of grocery retailing. There are three essential motivations resulting in this topic. Firstly, increasing diversity in the UK leads to significant exposure between immigrants and members of home country. Secondly, as the ethnic-minority retail entrepreneurs are facing with greater expansion of conventional retailing, ‘breakout’ of niche market and ‘breakthrough’ more potential mainstream segment is vital for further development. Lastly, lacking of academic research on mainstream consumers’ behaviours toward ethnic-oriented commodities is the major stimulation for conducting this research. Fundamental groundwork for the study is provided by literature review which focuses to explore three main topics: the crossover of ethnic foods into British cuisine, ethnic minority-owned business in the UK, particularly grocery retailing and the recent grocery shopping habits of British consumers. For developing an in-depth understanding of consumers’ insights on this issue, qualitative method was employed in the form of depth-interviews. In purpose of obtaining holistic view, British consumers and ethnic retailers were selected to participate in the semi-structure interviews. Through the comprehensive analysis of the findings, it is found that the influential factors which either motivation and impede British consumer toward patronizing ethnic grocery stores highly depends on the individual characteristic of the customers, particularly in term of diversity-seeking attitude. Besides, the research also observes that in-store experiences which drive customer satisfaction and shopping attitude are highly involved with hedonic-shopping value. From these findings, managerial implications are provided with strategies for ethnic grocery retailers to better reach British customers.